Outcomes of Dental Implants in Routine Clinical Practice: A Retrospective Multicenter Study - Funda Goker; Pooja Mali Rai; Daniele De Santis; Maurizio Colombo; Lorenzo Gornati; Emanuele Savoini; Sourav Panda; Massimo Del Fabbro (International Journal of Dentistry)
Conclusion: Following current guidelines for implant therapy, consisting of proper diagnosis and personalised treatment plan and maintenance, and adhering to implant system manufacturer’s recommendations, it is possible to achieve satisfactory clinical and radiographic outcomes in routine practice.